Dynamic quality of service for different flow types in SDN networks. (30th April 2021) - Lima, Alessandro; Alchieri, Eduardo
The structure of the internet makes it difficult to implement Quality of Service (QoS) in different flows generated by many different applications with different demands. One of the challenges is the lack of technical knowledge and the difficulty of configuring network equipment with many proprietary technologies. Software Defined Networks (SDN) is a good alternative to mitigate these problems. However, SDN technology itself still suffers from the limitation of solid QoS mechanisms, especially considering flows classified as elephant (large data volume), cheetah (high throughput) and alpha (large bursts). Aiming to fill this gap, this work proposes a new SDN service, called QoS-Flux, that receives network information from the data plane to apply different QoS algorithms and filters to dynamically deal with different flows. Experimental results show that QoS-Flux significantly improves the QoS metrics of delay, jitter, packet loss, and bandwidth in a SDN.